Pengaruh Keseimbangan Kehidupan Kerja terhadap Kinerja Wanita Karir yang Dimediasi Kelelahan Kerja dan Dimoderasi Dukungan Organisasi dan Dukungan Keluarga - Lelly Christin; Nadia Stefanie Destiana; Dian Puspita Sari; Sarfilianty Anggiani (Business Management Journal, 2022)
This study aims to empirically examine the effect of work balance, organizational support, job burnout and career women's performance. Analysis of the variables used in this study there are five variables, namely work-life balance, organizational support, family support, work fatigue and performance. In this study, non-probability sampling was used, namely the sample taken was not given the same opportunity or opportunity for each member of the population to be selected as a sample. The sampling technique used is purposive sampling. Of the 98 respondents who filled out the questionnaire, only 64 respondents met the criteria for this research sample. The sample used in this study are career women who occupy managerial positions. The data collected is using a questionnaire with a Likert scale. From this study, only two significant hypotheses were produced, namely the existence of a significant direct effect of work-life balance on the performance of career women, and organizational support moderating the effect of work-life balance on job burnout.